VARIABILITAS DALAM TERJEMAHAN - M.R. Nababan (Kementerian Sekretariat Negara Republik Indonesia, 2014)
The present article reports a comparison between two versions of translation in order to reveal variabilities in translation. Research data analysis indicates that to a certain degree the two versions of the translation under investigation are divergent from one another in relation to the ways the message of source text was rendered into the target texts and to their quality. The first version tended to be oriented to the target language evidenced by 1) the provision of additional information in the form of annotation, 2) the adaptation of concepts or cultural terms, 3) the use of specific equivalence, 4) the rendetion of address forms based on the context of target language, and 5) the use of equivalence on the basis of pragmatic force considerations. In addition, the two versions of the translation have the same level of accuracy, the translation produced by Dian Vita Elliyati is more acceptable and readable for the target readers. This is due to the fact that she is sensitive towards the contexts of situation and culture as well as to the function and purpose of the translation.